The relationship between school principal leadership style and teacher efficacy : a case study / Yein @ Ian Bilun - Bilun, Yein @ Ian (2012)
A principal's role in school is very important in maintaining or diminishing teacher efficacy. Henceforth this study was conducted with the aim to examine the relationship between school leadership style and teacher efficacy especially in the remote or rural secondary schools in Sri A man district, Sarawak, Malaysia. The descriptive correlative study involved 108 teachers from one of the secondary schools in Sri Aman district, Sarawak, Malaysia. The study was a case study that employed a mixed method approach where data were collected via a Multifactor Leadership Questionnaire (MLQ), Ohio State of Teachers' Efficacy Scale (OSTES) and semi-structured interviews. To analyze the data, a SPSS Version 16.0 was used for descriptive and inferential statistics to examine the strength and relation direction between the two variables namely the principal leadership style and teacher self-efficacy. The overall reliability for MLQ was established at 0.74 - 0.91 alpha level while OSTES at 0.86 - 0.90 alpha level. The findings revealed that teachers favored transformational leadership style and the least was laissez-faire leadership style. Findings also indicated that there was no significant difference among the three leadership style on the efficacy scale. However, there was a significant difference on classroom management and instructional strategies in leadership style. The findings also indicated that there was no clear relationship emerged from teachers' view between high efficacy and low efficacy teacher groups on the efficacy scales of student engagement or instructional strategy. The findings imply that the school principal must be aware that teachers must possess strong self efficacy to enable them to lead and guide their students to achieve an excellent results. Besides, teachers must be provided with proper assistance and guidance when needed, give motivation and encouragement and keep abreast with latest technologies and skills.